A New Era for Ubicomp Development - Hodges, Steve; Villar, Nicolas; Scott, James; Schmidt, Albrecht (IEEE Pervasive Computing, 2012)
Over the past decade, a range of platforms have become available that can help researchers and hobbyists prototype new concepts in the ubiquitous computing domain. Such platforms, including Arduino and Microsoft .NET Gadgeteer, lower the barrier to entry for building custom electronic devices and facilitate plug-and-play prototyping. They also bring sophisticated software tools and abstractions—commonplace in desktop computer software development—to the embedded arena, letting users quickly and easily create devices with complex behaviors. Combined with recent advances in rapid-physical-prototyping technologies, it’s now possible to control the form factor of these prototypes and—for the first time—create devices with form and function approaching consumer expectations for electronics devices. These technologies might ultimately democratize embedded concept development, supporting a more diverse ecosystem of ubicomp products.